STUDI HABITAT BUAYA SENYULONG (Tomistoma schlegelii) DI SUNGAI SEKONYER TAMAN NASIONAL TANJUNG PUTING KALIMANTAN TENGAH - Saputro, M Bakti; Rifanjani, Slamet; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2020)
Senyulong (Tomistoma schlegelii) are crocodiles that have a unique morphology with shape of the snout in its mouth. This species based on IUCN Red List classified by endangered category (IUCN 2004). This study aim to determine characteristics ofSenyulong Habitat in Sekonyer river, Tanjung Puting National Park Central Kalimantan using by Purposive Sampling in discovery spot or ex crocodile nest, Parameter analyzed by important value index (INP), dominance index (C), index species diversity (H), species abundance index (e), and species similarity index. The results showed the abiotic water habitats in the river water pH 6 which indicated normal, an average of depth 4.5 meters and a water temperature 23.90 ÂºC. Biotically False Gharial likes the habitat of aquatic plants such as Rasau (Pandanus tectorious), water lily (Hanguana malayana) for sheltering. False gharial aquatic food habitats such as Toman fish (Channa gachua), Gabus (Channa striata) and Runtuk (Channa luchius) Baung (Mystus wyckii), Lais (Lais hexamena). Abiotically terrestrial habitats contain sandy clay texture and histosol soil types with 6 soil acidity, with 78% air humidity and the average temperature of 29ÂºC. Biologically, Senyulong terrestrial habitat formed by buffer zone with large tree with wide canopy and several types of terrestrial animals Senyulong food such as long-tailed monkeys, orangutans, and wild pigs. The terrestrial habitat of False Gharial is an important place to spawning ground by placing its eggs under a large buttress tree and covering the nest with leaf litter to keep it warm to camouflage egg predators such as to monitor lizards.Keyword: Terrestrial Habitat, Aquatic Habitat, Senyulong, Tanjung puting National Park